TINDAK PIDANA PEMBUNUHAN BERENCANA DI KABUPATEN SAMPANG STUDI DI PENGADILAN NEGERI SAMPANG - Abdus Salam (Dinamika, 2020)
Criminal law positive Indanesia, which is valid until today, still lists the sanctions the death penalty as stipulated in the punishment of the principal.In Indonesia, death penalty is the criminal main the oldest that still survives to this day and it is also possible for the foreseeable future so that criminal acts that occur may be subject to criminal sanctions die.The number of criminal offenses that can be punished a death penalty and procedures for the implementation of the death penalty is always subject to change from time to time, along with the dynamics of the social life of the people who continue to experience changes from day to day which shows that the dynamics of social change continue to run dynamically.Criminal cases of premeditated murder with the use clurit slashed the victim repeatedly so that the victim covered in blood and result in loss of life as well as death of the victim intentionally and with a plan, in the year 2013 in the district of Sampang.As for the causes and the modus operandi of criminal acts of premeditated murder, among others, due to his pride being insulted, disputes possessions to infidelity, for it is a settlement of the case through the existing law, through the considerations to can be found a kejahantan the cance ansuatu criminal acts of premeditated murder, to provide a deterrent effect so as not to recur the crime of premeditated murder is, should judges impose sanctions death penalty for the perpetrators of the crime with planned. Keywords : Crime, Murder, Carok.